A key to Brazilian genera of Plecoptera (Insecta) based on nymphs - Olifiers, Martina H.; Dorvillé, Luís F.m.; Nessimian, Jorge L.; Hamada, Neusa (Zootaxa, 2004)
An illustrated key is proposed for identification of nymphs of Plecoptera genera reported from Brazil: Anacroneuria Klap lek, 1909; Macrogynoplax Enderlein, 1909; Enderleina Jewett, 1960 Kempnyia Klap lek, 1916 (Perlidae), Tupiperla Froehlich, 1969; Paragripopteryx Enderlein, 1909; Gripopteryx Pictet, 1841 and Guaranyperla Froehlich, 2001 (Gripopterygidae).